Relationship Between Coping Strategies and Levels of Anxiety Among Diabetes Mellitus Patients In Makassar - Napolion, Kens; Siatang, Weni; Ekawati, Dian (KnE Life Sciences, 2021)
Diabetes mellitus is a chronic disease that has a negative physical and psychological impact on sufferers,. Anxiety is a reaction to illness as a threat; coping strategies are changes made by individuals in their attitudes, thoughts and feelings towards the stresses they are facing. The purpose of this study is to determine the relationship between coping strategies and anxiety levels of diabetes mellitus sufferers. The research method used was an Analytical Survey with a Cross-Sectional Study approach and data collected via a questionnaire consisting of 20 statements to assess the patient’s coping strategies and 14 statements to assess the patient’s anxiety level. This research was carried out at the Internal Medicine Department of the Bhayangkara Mappaoudang Hospital in Makassar. From the results of this study obtained from 42 samples, 24 respondents have adaptive coping strategies with mild anxiety (57.1%), with 10 respondents displaying moderate anxiety (23.4%). Meanwhile, 2.4% of respondents displayed a maladaptive coping strategy with mild anxiety level, and 16.7% displayed moderate anxiety with a value of ρ = 0.004 which means ρ <α = 0.05. There is a relationship between coping strategies and anxiety levels of diabetes mellitus sufferers. It is recommended that future researchers examine other variables that have not been studied with a larger sample. Keywords: Coping Strategies, Anxiety, Diabetes Mellitus